A 15N tracing technique-based analysis of the fate of fertilizer N: a 4-year case study in eastern China. Issue 1 (2nd January 2017) - Hou, Maomao; Shao, Xiaohou; Jin, Qiu; Gao, Xiaoli
ABSTRACT: The fate of fertilizer N applied with different irrigation amounts in tobacco fields was quantitatively studied by applying 15 N double-labelled NH4 NO3 in lysimeters. The 15 N (fertilizer N originating from the fertilizer applied in 2011) in tobacco plants, 15 N in soils and 15 N loss were observed continuously from 2011 to 2014. The results showed that 21.6% of 15 N was utilized by tobacco plants, 72.1% remained in the 0–60 cm soil layer and 6.3% was lost from the soil–plant system after the first season's harvest (2011) of flue-cured tobacco. During the four seasons from 2011 to 2014, cumulative utilization of 15 N by tobacco plants was 34.3%, while 54.2% remained in the 0–60 cm soil layer, and 11.5% was lost via mechanisms such as leaching and volatilization. The fate of 15 N in terms of accumulation in plants and soils or losses from the soil–plant system from 2012 to 2014 was greatly affected by the fertilizer and irrigation management strategies in 2011. The results of this investigation suggest that the major amount of fertilizer N applied during the first season remains available in the soil for utilization by tobacco plants after 4 years.